2014
DOI: 10.1002/2014jd022083
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of aerosols and meteorological factors in Southwest China

Abstract: The spatial and temporal variations of aerosols and their relationships with meteorological conditions in Southwest China were studied to understand the aerosol-meteorology interactions. The spatial distribution of aerosols shows a strong "basin" effect with the highest values of Aerosol Optical Thickness at 0.55 μm (AOT, also denoted τ 0.55 ) (>0.70), fine-mode AOT (τ 0.55-fine ) (0.40~0.67), and coarse-mode AOT (τ 0.55-coarse ) (0.40~0.54), all observed in the Sichuan Basin. The temporal variation of seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Tai et al (2010), Shen et al (2018) all revealed that meteorological variables like temperature, relative humidity (RH), and wind speed explain much of the variations in PM 2.5 concentrations (> 50 %). Xiang et al (2019) and Gui et al (2019) found a negative association between planetary boundary layer height (PBLH) and PM 2.5 , and Kang et al (2014) found that fine-mode aerosols and air pressure were significantly correlated. In this study, to investigate the correlation between meteorological variables and the FMF, we implemented the generalized additive model (GAM).…”
Section: Meteorological Datamentioning
confidence: 99%
“…Tai et al (2010), Shen et al (2018) all revealed that meteorological variables like temperature, relative humidity (RH), and wind speed explain much of the variations in PM 2.5 concentrations (> 50 %). Xiang et al (2019) and Gui et al (2019) found a negative association between planetary boundary layer height (PBLH) and PM 2.5 , and Kang et al (2014) found that fine-mode aerosols and air pressure were significantly correlated. In this study, to investigate the correlation between meteorological variables and the FMF, we implemented the generalized additive model (GAM).…”
Section: Meteorological Datamentioning
confidence: 99%
“…The observed daily precipitation and maximum and minimum temperature data used in this study was collected from the SURF_CLI_CHN_MUL_DAY_V3.0 dataset, which was downloaded from the China Meteorological Data Sharing Service System ( http://cdc.nmic.cn/home.do ). This dataset contains daily measurements of eight meteorological factors (air pressure, temperature, precipitation, evaporation, etc 25 ) from 824 stations from January 1951 to July 2014. According to the dataset information ( http://cdc.nmic.cn/datasets.do?…”
Section: Methodsmentioning
confidence: 99%